Lipid-rich large plaques in a non-culprit left main coronary artery and long-term clinical outcomes. (15th April 2020) - Tashiro, Hiroshi; Tanaka, Akihito; Ishii, Hideki; Sakakibara, Keisuke; Tobe, Akihiro; Kataoka, Takashi; Miki, Yusuke; Hitora, Yusuke; Niwa, Kiyoshi; Furusawa, Kenji; Murohara, Toyoaki
Abstract: Background: An integrated backscatter (IB) intravascular ultrasound (IVUS) provides an information about tissue components and vulnerability of coronary plaques. The presence of vulnerable plaque in non-culprit lesion is associated with future clinical events. The purpose of this study was to assess the association between the characteristics of non-culprit left main coronary artery (LMCA) plaques evaluated by IB-IVUS and long-term clinical outcomes in patients undergoing percutaneous coronary intervention (PCI). Methods: Among the patients who underwent non-LMCA PCI, we studied 366 patients with adequate LMCA IVUS images. Conventional and IB-IVUS analyses of the LMCA segment were performed. Lipid-rich large plaque was defined as the presence of both a lager plaque volume and a higher percentage of the lipid component than the obtained median values. Major adverse cardiovascular events (MACE) included cardiac death, myocardial infarction, and unplanned revascularization. Results: The mean age of the patients was 68.5 ± 10.2 years, 79.8% were men. Median follow-up period was 6.0 years (IQR: 4.2–8.1 years). The incidence of MACE was significantly higher in patients with lipid-rich large plaques ( P  = .006). The incidence rates of cardiac death, myocardial infarction, and unplanned revascularization were significantly higher in patients with lipid-rich large plaques ( P  = .02, 0.004, and 0.02, respectively). Multivariate Cox regression analysis showed that the presence of a lipid-rich large plaque was significantly associated with MACE (HR: 1.74; 95%CI: 1.17–2.58; P  = .006). Conclusion: The presence of lipid-rich large plaques in a non-culprit LMCA can be associated with the long-term MACE in patients who have undergone PCI. Highlights: Lipid-rich large plaque in non-culprit LMCA was defined by IB-IVUS. Patients with lipid-rich large plaques were at a higher risk of adverse cardiac events. Patients with lipid-rich large plaques were at a higher risk of cardiac death and MI. Patients with lipid-rich large plaques were at a higher risk of unplanned revascularization.